Human Activity in Antarctica: Effects on Metallic Trace Elements (MTEs) in Plants and Soils - Jaime Tapia; Marco Molina-Montenegro; Camila Sandoval; Natalia Rivas; Jessica Espinoza; Silvia Basualto; Pablo Fierro; Luis Vargas-Chacoff (Plants, 2021)
Colobanthus quitensis (Kunt) is one of the two vascular plant species present in Antarctica and develops under severe environmental conditions, being found in both pristine and human-threatened environments. We determined the Cd, Cr, Cu, Mn, Ni, Pb, and Zn levels in C. quitensis roots, leaves, and soils of origin using flame atomic absorption spectroscopy. In January 2017, we collected samples from four geographical zones on the longitudinal gradient along which C. quitensis is distributed, starting from Punta Arenas (PAR) at the extreme south of mainland Chile and moving southwards to the Antarctic territory from King George Island (KGI) to Hannah Point Peninsula (PHA) and finally Lagotellerie Island (LAT). We used certified reference material to validate the plant tissues and soil samples we collected. The highest concentrations of metals that we measured in the soils and in the C. quitensis roots and leaves were in samples we collected at the KGI station, the zone with the greatest human activity. The lowest concentrations we measured were at the LAT station, an island with little human intervention and scarce fauna. The mean concentrations of metals in the roots and leaves of C. quitensis followed a similar order at all sampling locations: Mn > Zn > Cu > Ni > Pb > Cr > Cd. In contrast, in soil, they followed the following order: Mn > Zn > Cu > Cr > Pb > Ni > Cd. The concentration levels obtained for the different metals in the soil and plants tissue samples in this region of Antarctica indicated that the area was non-polluted. However, the metallic trace element (MTE) concentrations may be at an early stage of contamination, as described in other areas of the Antarctic, being a new threat to this continent.